(untitled) (The International Journal for Scientific Research, 2026)
The study aimed to investigate the influence of Activity Based Costing Style on Improving Performance: Examining the modifying role of Modify Balance Scorecard at Sudanese Banks. The problem of the study focuses on a decrease of Improving Performance level at Sudanese Banks because of unawareness of implementing modern Managerial Accounting Styles. Three hypotheses were developed and a questionnaire was designed. After data collection and analysis from the respondents, the study reached up to modifying Modify Balance Scorecard relationship between Activity Based Costing style and Improving Performance with a change in the determination coefficients of (0.132). The study recommended there is a need to increase leadership & employees awareness in the importance of Activity Based Costing style, Modify Balance Scorecard & Improving Performance.